MEDIUM-TERM PREDICTION OF EARTHQUAKES FROM A SET OF CRITERIA: PRINCIPLES, METHODS, AND IMPLEMENTATION - Zavyalov A.D. (My University, 2005)
This paper presents results obtained in 1980-2002 from studies of various aspects of earthquake prediction in relation to the development of a method of medium-term prediction from a set of criteria.
Keywords: PREDICTION OF EARTHQUAKES; MEDIUM-TERM PREDICTION; CRITERIA